DIMENSI MORALITAS TERHADAP HUKUM - Faturachman, Renaldi; Muhammad Rizki, Dava; Al Faridzi, Salman (IBLAM LAW REVIEW, 2022)
The law cannot stand alone without morality so that the law created is able to provide order and comfort so that the law is far from arbitrary. Morality can be equated with order and has human objects of action which are ordered to each other and for certain purposes. The idea of ​​value (good or bad) is at the core of every moral system since the concept of value is the main concept in our order of practical concepts, i.e. the highest in its genus. There is a reciprocal influence between law and morals in various aspects of human life, there is a moral contribution to law and a legal contribution to morals. The morality of a society also affects legal products, while the law affects the good and bad views of that society. Laws bind everyone as citizens, but morality treats people only as individuals. One of the legal paradigms is value so that law can be seen as a value figure as well. Law as the embodiment of values ​​implies that its presence is to protect and promote values ​​that are upheld by society. In the sociology of law, such conflicts are explained by the interaction between certain values ​​and the social structure in which those values ​​are carried out. The purpose of this study is to answer questions that have not been answered by previous researchers. The research method in this study uses a normative juridical research method in which the search for data uses a literature review.